Residual photoreceptors affect the response of a degenerate retina to electrical stimulation - Keith Ly; Mohajeet B. Bhuckory; Davis Pham-Howard; Anna Kochnev Goldstein; Nathan Jensen; Daniel Palanker (Proceedings of the National Academy of Sciences, 2026)
Photovoltaic subretinal prosthesis can restore central vision in patients blinded by age-related macular degeneration with letter acuity matching its 100 µm pixel size. Improving resolution requires smaller pixels, but to still reach the target neurons, electric field should be less confined. However, wide-spreading field may engage adjacent photoreceptors and alter the visual perception. We studied the effects of residual photoreceptors on retinal responses to electrical stimulation using monopolar and bipolar photovoltaic arrays implanted subretinally in Long Evans rats with local photoreceptor loss, and compared that to RCS rats lacking all photoreceptors. Patterned retinal activation (880 nm, 0.5 to 10 ms) was assessed using visually evoked potentials under scotopic and photopic conditions, with and without the intravitreal injection of neurotransmitter blockers. Results were analyzed using a computational model of photoreceptor activation by various electric field configurations. We observed two mechanisms of photoreceptors engagement in electrical activation of the degenerate retina: 1) Dark-adapted photoreceptors near the implant can be simulated directly by a negative electric potential of the common return electrode along the edge of the array. 2) Light-adapted photoreceptors can reduce the stimulation threshold of bipolar cells within about 100 mm from the implant’s edge. Both effects may lead to reduced perceptual uniformity. Bipolar pixels with local return electrodes generate better confined electric fields than monopolar arrays and thus are less affected by the nearby photoreceptors. However, even such implants should be placed a few hundred micrometers from the edge of scotoma to minimize the unintended percepts.